TEACHERS' PROBLEMS IN IMPLEMENTING THE INDEPENDENT LEARNING CURRICULUM IN GRADE V STUDENTS OF SDIT INSAN GEMILANG SIGI - Ayu Lestari; Askar Askar; Elya Elya (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2025)
Roblematics is an obstacle or problem that still creates a problem that cannot yet be solved, so that achieving the goal becomes hampered and not optimal. The purpose of this study is to determine the Implementation of the Independent Learning Curriculum and to determine the teacher's efforts in overcoming the problems of the Independent Learning Curriculum in class V SDIT Insan Gemilang Sigi.This thesis is entitled "Teacher Problems in Implementing the Independent Learning Curriculum for Class V Students of SDIT Insan Gemilang Sigi".This type of research is field research using a descriptive qualitative approach. The data collection techniques used are observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and data verification. Based on the results of this study, it shows that: 1) SDIT Insan Gemilang Sigi School has implemented the Independent Learning Curriculum but is implemented gradually. 2) Problems faced by teachers in implementing the Independent Learning Curriculum, namely: lack of teacher readiness in facing the new challenges of the Independent Learning Curriculum, including: not all teachers understand the Independent Learning Curriculum, weak mastery of teachers in using Information Technology (IT), teachers have difficulty in making so many learning devices, especially teaching modules. 3) Efforts implemented by teachers in overcoming problems in implementing the Independent Learning Curriculum are to participate in socialization and training on the Independent Learning Curriculum, teachers take the initiative to train themselves to increase their potential capacity in facing the new challenges of the Independent Learning Curriculum, in making teaching modules teachers can use teaching modules provided by the education government as an example. The implications of the results of this study are that schools are expected to pay more attention to teacher development in the process of implementing the Independent Learning Curriculum so that the learning process can run in accordance with the Curriculum that is currently being